China’s Vaccine Diplomacy in South Asia: Geopolitical Perspective - Tanwar, Priyanka (Asian Journal of Pharmaceutics (AJP), 2023)
For major nations to increase their geopolitical influence around the world, health diplomacy has remained a crucial component of their foreign policies. Given the outbreak of COVID-19, the inadequate health-care systems, even of the developed countries, have been exposed. Although China was blamed for the origination of COVID-19, concomitantly, the same nation has utilized the emergency in the global health field to further its geopolitical hegemonic influence by putting its diplomacy in the area of global health. On April 27, 2021, Wang Yi, the Chinese foreign minister, participated in a video conference together with his colleagues from Sri Lanka, Afghanistan, Bangladesh, Nepal, and Bangladesh. In an effort to coordinate efforts and talk about Chinese aid in the fight against COVID-19 in neighboring nations and post-pandemic recovery, a virtual conference was held. Chinese actions in the area since the coronavirus outbreak have emphasized Beijing’s efforts to strengthen its soft power and diplomacy. The article’s major conclusion is that China increased its global influence by pursuing health diplomacy to the greatest possible extent. It focuses on China’s use of soft power through its diplomatic efforts in global health. It also looks at how India’s own problems have given China more room to operate in the area.